Who is mobilized to vote by short text messages? Evidence from a nationwide field experiment with young voters - Hirvonen Salomo; Lassander Maarit; Sääkslahti Lauri; Tukiainen Janne (Aboa Centre for Economics, 2025)
We conduct a large-scale randomized controlled trial to evaluate the effectiveness of short text messages (SMS) as a tool to mobilize young voters, and thus, ameliorate the stubborn gap in political participation between younger and older citizens. We find that receiving an SMS reminder before the Finnish county elections in 2022 increases the probability of voting among 18-29 year-old voters by 0.9 percentage points. Moreover, we observe that the most simplified message is more effective than messages appealing to expressive or rational motivations to vote. Using comprehensive administrative data and data-driven machine learning methods, we also examine treatment effect heterogeneity and spillover effects. We document that SMS based mobilization of voters does not only reduce existing social inequalities in voting between the age cohorts but also among the young citizens. Moreover, we remarkably find that over 100 percent of the direct treatment effect spilled over to non-treated household members. Our results highlight the importance of understanding spillover effects and treatment effect heterogeneities in the evaluation of get-out-the-vote interventions.